Lauraceae endémicas del Perú - León, Blanca (2006)
The Lauraceae, a characteristic family of Peru’s eastern montane forests are represented in Peru by 16 genera and 247 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004). Here we recognize 55 endemic species included in 11 genera. Nectandra and Ocotea are the genera with the largest number of endemic species. These endemic taxa, mostly trees and shrubs, are found mainly in the Humid Lowland Amazonian Forest and Very Humid Montane Forest regions, between 125 and 3100 m elevation. Nine of these species have been recorded to date in the Peruvian protected areas system.